Pengaruh Fear of Missing Out Terhadap Digital Well-Being Pada Pengguna Tik-Tok - Khansa Bella Putriyanto; Komarudin Komarudin (Jayapangus Press, 2026)
This study is motivated by the rising use of TikTok, which often triggers symptoms of Fear of Missing Out (FoMO) and is suspected to affect users’ levels of Digital Well-Being. The current inability of many adolescents to manage their time and social resources wisely can lead to disruptions in real-life functioning, prompting this research to examine the influence of FoMO on Digital Well-Being among TikTok users in the Special Region of Yogyakarta. Using a quantitative approach with accidental sampling, the study involved 100 active TikTok users and employed two researcher-adapted scales: Przybylski’s FoMO scale and Smits’s Digital Well-Being scale. Data were analyzed using normality tests, linearity tests, Pearson correlation, and simple linear regression through SPSS 25. The results reveal a strong and significant relationship between FoMO and Digital Well-Being. Most participants showed moderate levels of both FoMO and Digital Well-Being, indicating that higher FoMO is associated with lower perceived Digital Well-Being among TikTok users. This study fills an existing research gap by examining FoMO directly in relation to digital well-being within the context of TikTok usage.